The kinds of knowledge involved in nursing home care: integrative review of the scientific production - Luciane Favero; Tatiana Braga de Camargo; Maria Helena Lenardt; Verônica de Azevedo Mazza; Maria Ribeiro Lacerda (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
It is an integrative review on Brazilian Nursing scientific production which objectifies to recognize the different kinds of knowledge involved in nursing home care productions. The research study took up January/1998 to March/2008 and resulted in the analysis of 41 productions (34 articles, a PhD thesis, a post-graduation monograph, one graduation paper and four publications in Congress annals), distributed in the following database: MEDLINE, LILACS, SciELO and BDENF. The results evidenced that scientific knowledge was present in 100% of the studies followed by political (63.4%), ethical (56.1%), artistic (19.5%), philosophical and common sense (9.7% each), religious (7.3%), esthetical and mythical knowing (2.4% each). It can be concluded that the professionals in the researched studies use such knowing to deliver nursing home care, however there is a need to broaden studies on the theme in order to bring together scientific knowledge and the other kinds of knowing aforementioned, aiming to render clients and their families authentic, effective and through home care.